(untitled) (Research, Society and Development, 2020)
This article aims to present a didactic sequence for students of a private primary education school in Estância, Sergipe, using entrepreneurship as a tool for teaching chemistry. Entrepreneurial education is an effective method for developing specific skills and an exciting alternative to traditional education. Based on the concept that entrepreneurship is not a single, one-step method, but a set of organized actions and techniques, activities were proposed based on the students’ desires and motivations. The fundamentals and modern theories that involve entrepreneurial education and its application at school were analyzed. Through the proposed strategy, important chemical concepts such as mixtures, organic functions, atomic models, solutions, and emulsions were performed with students. With this, the present study concluded that entrepreneurial education could go beyond teaching concepts and methodologies; it focuses on learning, with the student taking the lead in his entrepreneurial journey.